P135. Transient Rho kinase inhibition enhance the generation of human induced pluripotent stem cells in feeder-independent, serum-free culture system - Kevin, Wing-Hon Lai; Jenny, Chung-Yee Ho; Kong, Chi-Wing; Lee, Yee-Ki; Ng, Kwong-Man; Au, Ka-Wing; Chan, Yau-Chi; Lau, Chu-Pak; Tse, Hung-Fat; Siu, Chung-Wah (Differentiation (London), 2010)
Induced pluripotent stem cells generated from human adult somatic cells through reprogramming hold great promises for future regenerative medicine. However, exposure of human induced pluripotent stem cells to animal feeder cells and serum in the process of their generation and maintenance imposes risk of transmitting animal pathogens to human subjects, thus hindering the potential therapeutic applications. Our aim was to generate patient-specific human induced pluripotent stem cells in a feeder-independent culture system with defined factors. Fresh human dermal fibroblasts obtained from two healthy volunteers were reprogrammed with a defined set of transcription factors using lentiviral vectors in a feeder-independent cell culture system using mTeSR1 medium. At day 6, the Rho Kinase inhibitor (ROCKi) (Y27632) was added for 24 h to facilitate the iPS cell clusters formation. iPS cells generated were characterized by immunostaining, FACS, kayotyping and teratoma formation. Two new human induced pluripotent stem cell lines were generated from dermal fibroblasts of the two subjects under feeder-independent culture system with defined factors. Addition of Y27632, the ROCKi can significantly increase in the number of iPS-like clusters per ten thousands cells (Patient 1: 9±1.4 vs 2±1.1, Patient 2: 14.7±4.2 vs 3.3±1.5). The resultant cells maintained normal karyotypes and expressed a panel of pluripotency markers including stage-specific embryonic antigen (SSEA)-4 (99.1±1.1%), tumor-rejection antigen (TRA)-1-60 (93.8±3.6%), and (TRA)-1-81 (99.7±0.1%), and alkaline phosphatase. In addition, these cells can be induced to differentiate along lineages representative of the three embryonic germ layers upon formation of embryoid bodies, indicating their pluripotency. Furthermore, subcutaneous transplantation of these cells into immunodeficient mice resulted in teratoma formation. It suggested that transient ROCK inhibition can significantly increase the reprogramming efficiency of human iPS cells under feeder-free and serum free condition. In additions, the resultant cells resemble the characteristics of human embryonic stem cells and can differentiate into different types of tissue.